Geographic note on species of the genus Upa Kimsey, 1991 (Hymenoptera: Tiphiidae, Thynninae) in the Atlantic Forest, Brazil - Justino, Cintia Eleonora Lopes [UNESP]; Santos, Eduardo Fernando dos; Noll, Fernando Barbosa [UNESP] (My University, 2013)
Upa Kimsey is a poorly known genus of Tiphiidae with seven species. This genus has records in forest areas and in this paper we present new records to four species. All specimens were collected by malaise traps in four areas of Atlantic Rain Forest and three of Atlantic Semi-deciduous forest, mainly from high and mid-elevations. The new records indicate that species of Upa are not as rare as others genera of Tiphiidae, which are virtually unknown in many Neotropical regions.